1998
DOI: 10.3354/dao033143
|View full text |Cite
|
Sign up to set email alerts
|

Impact of low water temperature on the development of Anguillicola crassus in the final host Anguilla anguilla

Abstract: ABSTRACT. The effect of low water temperatures on the development and viability of larval and adult Ang~lillicola crassus (Nematoda) in the final host Anguilla ang~lilla was studied. European eels were experimentally infected with A. crassirs and then maintained for 4 mo at 4,9, 10 and 19°C. Larval development showed a temperature-dependent pattern and was significantly retarded at low temperatures. Third-stage larvae survived a 4 mo period at 4'C without belng affected, although they were not able to invade t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 13 publications
4
68
1
Order By: Relevance
“…The distribution of Anguillicola crassus found in the present study does not appear to be limited by temperature, as has been suggested in other studies (Knopf et al 1998). Eels from the Penobscot River drainage are infected with A. crassus, and this system has similar annual water temperatures to the East Machias River, Maine, the northernmost site sampled within the USA, and to the southern Nova Scotia rivers.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The distribution of Anguillicola crassus found in the present study does not appear to be limited by temperature, as has been suggested in other studies (Knopf et al 1998). Eels from the Penobscot River drainage are infected with A. crassus, and this system has similar annual water temperatures to the East Machias River, Maine, the northernmost site sampled within the USA, and to the southern Nova Scotia rivers.…”
Section: Discussionsupporting
confidence: 64%
“…Eels from the Penobscot River drainage are infected with A. crassus, and this system has similar annual water temperatures to the East Machias River, Maine, the northernmost site sampled within the USA, and to the southern Nova Scotia rivers. Knopf et al (1998) proposed that American eels of the St. Lawrence River would not be affected by a northward expansion because low winter water temperatures would hinder the parasite's survival. They also state that L 3 stage larvae can withstand 4°C for periods up to 4 mo, with low temperature presumably causing delayed development and high mortality of the adult parasite phase within the eel.…”
Section: Discussionmentioning
confidence: 99%
“…Negative control sera were taken from 43 non-infected eels purchased from a commercial fish farm (Limnotherm, Bergheim, Germany). A spot-check of 15 eels was performed to confirm that eels from this source were free of Anguillicola crassus as stated in previous studies (Würtz et al 1996, Knopf et al 1998, Sures et al 1999a). Blood samples were drawn from the caudal vein without using an anaesthetic or anticoagulant.…”
Section: Source Of Antigens Adult Anguillicola Crassus Andmentioning
confidence: 99%
“…The intestinal wall was rinsed with PBS to remove any intestinal content. L 3 of A. crassus were produced following Haenen et al (1994), modified as described recently (Knopf et al 1998). The L 3 were used completely for the preparation of somatic larval antigen.…”
Section: Source Of Antigens Adult Anguillicola Crassus Andmentioning
confidence: 99%
“…Thus, low pre valences are more often found as sociated with high latitudes. Be cause latitude is a reasonable proxy for mean water temperature, this tends to give support to the 'temperature limit' hypothesis, according to which the pa ra site's geographic ex pansion would stop under high latitudes (Knopf et al 1998). However, this trend observed at a global scale does not preclude the co lonization of the northernmost range of the eel hosts, as recently documented by the occurrence of A. crassus above 60°N (e.g.…”
Section: Relationships Between Parasite Load and Water Salinitymentioning
confidence: 93%